Intergraded CBT and MI for substance abuse in psychotic patients : a randomized controlled trial - Stefán Þorri Helgason 1991- (2023)
Integrated CBT and MI is an evidence-based psychosocial treatment that has been demonstrated to be effective in enhancing motivation to change substance-related behavior and fostering more helpful coping strategies toward substance abuse. The current randomized controlled trial (RCT) aimed to assess the efficacy of an integrated Cognitive Behavioral Therapy and Motivational Interviewing (CBT+MI) intervention in promoting helpful attitudes towards abstinence from substance use, motivation to change alcohol and substance abuse-related behavior, alleviating anxiety, and depression symptoms, and improving the quality of life in individuals with dual diagnosis (DD) of psychotic disorders and substance use disorders. A total of 21 participants with DD were enrolled from the psychosis service at Landspítali, The National University Hospital of Iceland. Participants were randomly assigned to either a treatment group receiving CBT+MI alongside treatment as usual (TAU) or a control group receiving only TAU. Results revealed that CBT+MI led to lower anxiety scores compared to TAU and suggested improvements in depression scores and quality of life. This may be due to participants' increased skills in handling challenging emotions such as anxiety. However, the study did not find any significant differences in enhanced motivation to change substance and alcohol-related behavior or when prompting more helpful attitudes toward abstinence from substance abuse between the intervention group and control group. Further research is needed to explore the potential benefits of this intervention approach with larger and more diverse samples.